Integration Science and Religion: An Analysis in Islamic Higher Education - Nuryantini, Ade Yeti; K, Karman; Holik, Abdul (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractThe integration of Islamic values in the learning process at UIN Sunan Gunung Djati Bandung has become the hallmark of the campus. The Islamic values integrated into the learning process by providing the verses from the Quran for the concepts studied. This study aims to analyze the ability of students used to live in an Islamic boarding school (pesantren) and those who haven’t yet live in an Islamic boarding school in identifying the verses of al-Quran related to some concept of physics. The research was conducted through observation in classrooms and analysis of students’ assignment on identifying. The results showed that generally, students have a decent ability in identifying Qur'anic verses related to the concept of physics. The students' ability appeared not to be influenced by the pesantren educational background. However, largely students are not able to interpret the verses of the Qur'an related to the physics concept in depth.AbstrakIntegrasi nilai-nilai Islam dalam proses pembelajaran di UIN Sunan Gunung Djati Bandung telah menjadi ciri khas kampus. Integrasi nilai-nilai Islam ke dalam proses pembelajaran dapat dilakukan dengan menghubungkan ayat-ayat al-Quran dengan konsep-konsep yang dipelajari. Penelitian ini bertujuan untuk menganalisis kemampuan mahasiswa Prodi Pendidikan Fisika yang pernah tinggal di pesantren dan yang tidak pernah tinggal di pesantren dalam mengidentifikasi ayat-ayat al-Quran terkait dengan konsep fisika. Penelitian dilakukan melalui observasi di ruang kelas dan analisis tugas yang dikumpulkan dari mahasiswa ketika mengidentifikasi ayat-ayat Al-Qur'an yang berkaitan dengan konsep fisika. Hasil penelitian menunjukkan umumnya mahasiswa memiliki kemampuan yang layak dalam mengidentifikasi ayat-ayat Al-Qur'an yang berkaitan dengan konsep fisika. Kemampuan mahasiswa tersebut tidak dipengaruhi oleh latar belakang pendidikan di pesantren. Namun, sebagian besar mahasiswa tidak mampu menafsirkan ayat-ayat Al Qur'an yang terkait dengan konsep fisika secara mendalam.How to Cite : Nuryantini, A. Y.. Karman., Holik, A. (2018). Integration Science and Religion in Physic Subject: An Analysis in Islamic Higher Education. TARBIYA: Journal of Education in Muslim Society, 5(1), 11-18. doi:10.15408/tjems.v5i1.9508.